Efficacious interventions for improving the transition readiness of adolescents and young adult patients with chronic illness: A narrative review of randomized control trials assessed with the transition readiness assessment questionnaire - Takeuchi, Jiro; Yanagimoto, Yoshitoki; Sato, Yuki; Ochiai, Ryota; Moriichi, Akinori; Ishizaki, Yuko; Nakayama, Takeo (Frontiers in Pediatrics, 2022)
Objective: We inspected efficacious interventions to improve the transition readiness of adolescent and young adult patients with childhood-onset chronic illness using the Transition Readiness Assessment Questionnaire (TRAQ). Methods: Our narrative review was conducted on all randomized control studies assessed with TRAQ for outcome measurement before and after the interventions. We included all patients with chronic diseases. We searched eight electronic database(s): AMED Allied and Complementary Medicine, BIOSIS Previews, CINAHL, the Cochrane Library, EMBASE, Ichu-shi, Medline, Web of Science. The text words for the search of data sources were as follows: “(transition readiness assessment questionnaire OR TRAQ) AND 2011/01:2022/06[DP] AND (clinical AND trial OR clinical trials OR clinical trial OR random* OR random allocation).” More studies were identified from the references of our reported study. This data set was independently cross-checked by two reviewers. Results: We identified 261 reports and collected three articles. The target diseases were type 1 diabetes, congenital heart disease, cystic fibrosis, and inflammatory bowel disease. All the studies excluded patients with intellectual disability. The age of the participants was distributed between 12 and 20 years. Nurse-provided web-based intervention of transition readiness was constructed by digital resources in two studies. The intervention ranged from 6 months to 18 months. All the interventions were efficacious in improving transition readiness assessed with TRAQ scores, except for the self-advocacy score. Conclusions: We obtained three randomized control studies with TRAQ for outcome measurement. In two studies, web-based and nurse-led organized intervention was shown to improve transition readiness.